Efficacy of osteoporosis pharmacotherapies in preventing fracture among oral glucocorticoid users: a network meta-analysis. Issue 6 (June 2016) - Amiche, M.; Albaum, J.; Tadrous, M.; Pechlivanoglou, P.; Lévesque, L.; Adachi, J.; Cadarette, S.
Abstract Summary Efficacy of osteoporosis medication is not well-established among patients taking oral glucocorticoids. We assessed the efficacy of approved osteoporosis pharmacotherapies in preventing fracture by combining data from randomized controlled trials. Teriparatide, risedronate, and etidronate were associated with decreased vertebral fracture risk. Introduction Several osteoporosis drugs are approved for the prevention and treatment of glucocorticoid (GC)-induced osteoporosis. However, the efficacy of these treatments among oral GC users is still limited. We aimed to examine the comparative efficacy of osteoporosis treatments among oral GC users. Methods We updated a systematic review through to March 2015 to identify all double-blinded randomized controlled trials (RCTs) that examined osteoporosis treatment among oral GC users. We used a network meta-analysis with informative priors to derive comparative risk ratios (RRs) and 95 % credible intervals (95 % CrI) for vertebral and non-vertebral fracture and mean differences in lumbar spine (LS) and femoral neck (FN) bone mineral density (BMD). Treatment ranking was estimated using the surface under the cumulative ranking curve (SUCRA) statistic. A meta-regression was completed to assess a subgroup effect between patients with prior GC exposures and GC initiators. Results We identified 27 eligible RCTs examining nine active comparators. Etidronate (RR, 0.41; 95%CrI = 0.17–0.90), risedronate (RR = 0.30, 95%CrI = 0.14–0.61), and teriparatide (RR = 0.07, 95%CrI = 0.001–0.48) showed greater efficacy than placebo in preventing vertebral fractures; yet, no treatment effects were statistically significant in reducing non-vertebral fractures. Alendronate, risedronate, and etidronate increased LS BMD while alendronate and raloxifene increased FN BMD. In preventing vertebral fractures, teriparatide was ranked as the best treatment (SUCRA: 77 %), followed by risedronate (77 %) and zoledronic acid (76 %). For non-vertebral fractures, teriparatide also had the highest SUCRA (69 %), followed by risedronate (64 %). No subgroup effect was identified with regards to prior GC exposure. Conclusions Despite weak trial evidence available for fracture prevention among GC users, we identified several drugs that are likely to prevent osteoporotic fracture. Teriparatide, risedronate, and etidronate were associated with decreased vertebral fracture risk.